Process Intensification of Polyphenol and Flavonoid Extraction from Ant Nest (Myrmecodia pendans) via Ohmic Heating: Investigating Joule Heating and Electric Field-Time Interactions Using a Response Surface Methodology - Handayani Nofiyanti, Sri; Fajarini, Luh Dian Rna; Putra, I Gede Arie Mahendra; Arista, Yuvita Lira Vesti (Trends in Sciences, 2025)
Ant nest (Myrmecodia pendans) is a unique epiphytic plant native to the tropical forests of Eastern Indonesia, traditionally used by indigenous communities for its medicinal properties. It is characterized by its tuber-like structure, which serves as a natural habitat for ants and is believed to contribute to its rich content of bioactive compounds. This plant is particularly valued for its high levels of polyphenols and flavonoids, which are known for their antioxidant, anti-inflammatory and therapeutic effects. Ohmic heating is an innovative, energy-efficient extraction technique that utilizes electrical resistance to generate internal heat within conductive plant materials. This study applied ohmic heating as an innovative and energy-efficient extraction method to enhance the recovery of these bioactive compounds. Response Surface Methodology (RSM) with Central Composite Design (CCD) was used to optimize the extraction conditions. Two independent variables, holding time (90 - 270 s) and gradient voltage (20 - 60 V/cm), were investigated. Quadratic polynomial models were developed for total phenolic content (TPC), total flavonoid content (TFC) and extraction yield through multiple linear regression. The optimization using the desirability function indicated that the optimal extraction conditions were a holding time of 195.883 s and a gradient voltage of 52.761 V/cm, which predicted values of 256.145 mg GAE/g (TPC), 118.837 mg QE/g (TFC) and 38.154% extraction yield. Critically, the performance of the ohmic system was characterized based on electrical and thermal parameters. The initial electrical conductivity of the extraction medium ranged from 0.171 to 0.407 S/m, increasing with voltage and time. The temperature of the medium rose from 30 °C to a peak of 87 °C during treatment, indicating efficient internal volumetric heating. Corresponding energy consumption ranged from 0.0805 to 0.3045 kWh per batch, equivalent to 28.98 - 109.62 kJ per g of dry ant nest powder. These results confirm that ohmic heating enables rapid and energy-efficient extraction while preserving thermal sensitivity of bioactive compounds. HIGHLIGHTS The ant nest plant was studied for its phenolic and flavonoid content. RSM with CCD used to optimize ohmic heating extraction. Electrical conductivity, energy input and temperature rise were quantitatively assessed. Optimal extraction conditions yielded a high content of phenolics and flavonoids. Ohmic heating is efficient and eco-friendly for compound extraction. GRAPHICAL ABSTRACT